2017
DOI: 10.1186/s12974-017-0947-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective suppression of the JNK-MMP2/9 signal pathway by tetramethylpyrazine attenuates neuropathic pain in rats

Abstract: Background: Activated astrocytes release matrix metalloproteinase-2/9 (MMP-2/9) to induce central sensitization and maintain neuropathic pain. However, the mechanisms involved in the activation of MMP-2/9 on astrocytes during pain remain poorly understood. Meanwhile, there is a lack of effective treatment to inhibit the activation of MMP-2/9 on astrocytes. In this study, we aim to investigate the effect of tetramethylpyrazine (TMP), a natural compound with analgesic effects but unknown mechanisms, on MMP-2/9 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“… 68 70 As one of the most important members of the MAPK family, JNK was also found to be activated in neuropathic pain. 71 73 Our data illustrated that the alleviation of activated glia and pain behavior was ameliorated by the activation of α7nAChR. Therefore, we hypothesized that the effect might proceed through this complex downstream signaling pathway.…”
Section: Discussionmentioning
confidence: 84%
“… 68 70 As one of the most important members of the MAPK family, JNK was also found to be activated in neuropathic pain. 71 73 Our data illustrated that the alleviation of activated glia and pain behavior was ameliorated by the activation of α7nAChR. Therefore, we hypothesized that the effect might proceed through this complex downstream signaling pathway.…”
Section: Discussionmentioning
confidence: 84%
“…TMP and FA inhibit the activity of NADPH oxidase via ERK signaling pathway and NF-κB pathway respectively (Wong et al, 2007 ; Cao et al, 2015 ). (2) Antiinflammatory effects: TMP, senkyunolide A and ligustilide could down regulate the activation and proliferation of astrocytic, the production and bioactivity of tumor necrosis factor α (TNF-α), and the expression of cyclooxygenase-2 (COX-2) protein (Liu et al, 2005 ; Chung et al, 2012 ; Feng et al, 2012 ; Jiang et al, 2017 ). (3) Antiapoptotic effects: Ligustilide prevented neuronal apoptosis in both parietal cortex and hippocampus through regulation of mitochondrion metabolism (Feng et al, 2012 ) TMP could decrease the levels of miR-214-3p and increase the expression level of Bcl2l2 (Fan and Wu, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Double labeling with the tracers fast blue and horseradish peroxidase-labeled gold underwent retrograde transport from the site of injury and revealed that c-Jun protein expression was confined to injured neurons ( 34 ). Activated c-Jun in the dorsal root ganglion (DRG) contributes to the pathogenesis of neuropathic pain induced by CCI ( 35 ), and neuropathic pain is alleviated by inhibiting the mitogen-activated protein kinase 8 (JNK)/c-Jun signal pathway ( 36 , 37 ). Furthermore, Plau mRNA is abundantly expressed by many neurons in the peripheral and central nervous system ( 38 ).…”
Section: Discussionmentioning
confidence: 99%